Cover Feature: New Insights into the Catalytic Activity of Cobalt Orthophosphate Co3(PO4)2 from Charge Density Analysis (Chem. Eur. J. 69/2019). Issue 69 (17th October 2019) - Keil, Helena; Hellström, Matti; Stückl, Claudia; Herbst‐Irmer, Regine; Behler, Jörg; Stalke, Dietmar
Abstract : Solid‐state catalysis is the most important sustainable principle in chemical production. It lowers energy consumption, avoids waste and in many cases even volatile organic compounds as solvents. Experimental charge density determination in combination with computational methods pave the way to discriminate inactive against active solid‐state surfaces and assign catalytically active sites. This work investigated Co3 (PO4 )2 and identified the (011) face to be best suited for catalysis. Five‐fold coordinated Co ions in close proximity to advantageously oriented electron depletion sites suit the reactant's oxygen‐lone pairs most for chemisorption and heterogeneous C−H activation. More information can be found in the Full Paper by D. Stalke et al. on page 15786 .